ANALISIS YURIDIS PERLINDUNGAN HUKUM HAK CIPTA LAGU TERHADAP USAHA KARAOKE BERBAYAR DI KOTA BATAM - Muhammad Ilham Akbar; Idham Idham; Darwis Anatami (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
The existence of Law Number 28 of 2014 concerning Copyright, and Government Regulation Number 56 of 2021 concerning Management of Song and/or Music Copyright Royalties in the context of legal protection of song copyrights and also regulates the authority of the National Collective Management Institute to withdraw, collect , and distribute royalties from commercial users, The implementation of legal protection of song copyrights for paid karaoke businesses in Batam City is not running optimally due to the lack of socialization of legal protection of song copyrights, its implementation depends on the good faith of business owners, and ineffective sanctions arrangements, for that there needs to be an institution at the regional level that directly handles the legal protection process for song copyrights, and there needs to be strict sanctions for business owners who ignore their obligations to song copyrights.